Hair disorder in cosmetic dermatology venereology outpatient clinic of dr. Cipto Mangunkusumo Jakarta: socio-demographic and clinical evaluation - Lili Legiawati; Lis Surachmiati Suseno; Irma Bernadette S. Sitohang; Aditya Indra Pratama (PAGEPress Publications, 2022)
Background: Hair disorder has severe impacts on sociopsychology aspects. Currently, there are limited and outdated studies related to hair disorders in Indonesia. Aims: Our study aimed to provide an update regarding the epidemiology of hair loss commonly occurring in Indonesia Methods: This is a retrospective study that review hair disorder cases at the Cosmetic Dermatology Outpatient Clinic dr. Cipto Mangunkusumo National Central General Hospital between January 2017 to December 2019. Age, gender, family history, education, occupation, body mass index (BMI), comorbidities, and diagnosis of each patient were recorded. Results: From the 64 patients who were eligible for the study, hair disorders was found to be more prevalent in male 54.6% with a mean age of 26.41 + 12.8 years old and the highest age group of 18-39 years old 59.4%. There were 32 cases (50.0%) of alopecia areata (AA), 20 cases (31.2%) of alopecia androgenetic (AGA), 9 cases (14.0%) of telogen effluvium (TE), 2 cases of cicatricial alopecia (CA) due to lupus erythematosus (DLE) and 1 trichotillomania (TTM). Cases of TE were significantly higher in female patients. Cases of AGA in the study, mainly early-onset AGA (mean age 29.45 + 10.29 years old, 39.5% in 18-39 years old) showed a significant positive familial history. Conclusions: The most frequent type of hair disorder at dr Cipto Mangunkusumo National General Hospital Jakarta were AA, AGA, and TE, respectively with each disease showing a different socio-demographic and clinical profile.